Penerapan Metode Al-Kalam Dalam Meningkatkan Bacaan Al-Qur’an Di Tpa Al Ihsan Mubarak Cempaka Putih - Rizal, Rizal Rahmat (Communication and Islamic Broadcasting Studies IAIN Parepare, 2023)
Application of the Al-Kalam Method in increasing the recitation of the Koran at TPA Al-Ihsan Mubarak Cempaka Putih. (supervised by Ms. Nurhikmah, and Mr. Muhammad Ismail ) This study raises the issue of the application of the al-kalam method in increasing the reading of the Koran at TPA Al-Ihsan Mubarak Cempaka Putih with the sub-problem how the communication patterns of TPA teachers apply the al-kalam method in increasing the reading of the Koran at TPA Al-Ihsan Mubarak Cempaka Putih then the advantages of the al-kalam method in increasing the reading of the Koran at TPA Al-Ihsan Mubarak Cempaka Putih. This research uses descriptive qualitative which produces descriptive data in the form of other people's written or spoken words and observable behavior. The technique used is in the form of data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that the application of the al-kalam method in improving reading of the Qur'an uses interpersonal communication patterns and group communication and both of these communication patterns have the same type of communication, namely verbal communication and non-verbal communication. The advantages of the al-kalam method are that it is easy for children to understand and very fun for children and with the application of this method it will be easy to increase students' reading of the Koran at TPA Al-Ihsan Mubarak Cempaka Putih.